The Use of PPP Model In Enhancing the Students’ Speaking Ability - Badaruddin Badaruddin; Sahabuddin Sahabuddin (Universitas Sulawesi Barat, 2019)
Speaking is the ability to pronounce words in order to convey or stated intention, ideas, thoughsts, feeling and dificult to deal with students. There are some problems as causes of the students’ difficulties in speaking, such as they are afraid of making mistake, less convidence, seldom to communicate and cannot express their ideas. To solve the problems, the researcher suggests the use of PPP Model in learning process. Based on the previous explanation, the researcher formulates the objective of the research is to find out whether or not the speaking ability of the seventh grade students of SMP Negeri 9 Parepare can enhance through the Use of PPP Model In this research, the researcher applied quasi-experimental design, with two group namely experimental class and control class. The samples was chosen using cluster random sampling technique. The total numbers of sample were consisted of 55 students from two classes taken from the population of the seventh grade students of SMP Negeri 9 Parepare. The instrument used in this research was speaking test by record the students’ utterance. The data were analyzed by using t-test formula. The result of the data analyzed shows that the students’ speaking ability improved significantly. It was showed by the mean score of pre-test was 45.33 and the post-test was 72. 83. Besides, the mean score of the students in post-test (72.83) was higher than the Kriteria Ketuntasan Minimal (71) in SMP Negeri 9 Parepare and include good classification base on Dirjen Pendidikan Dasar dan Menegah (2005). In the same line, the result of t-test value was 2.102 and t-table value was 2.004 in post-test. It means that the t-test value (2.102) was higher than t-table value (2.004). Those indicate that H1 was accepted and H0 was rejected. It also shows there is a significant difference between the speaking ability of the students who were taught through the Use of PPP Model and the speaking ability of the students who were thought by Discovery Learning Model (Conventional Ways).